(untitled) (Research, Society and Development, 2018)
This paper discusses the importance of implementing the National System of Education, through the resumption of democratic principles advocated in the Manifesto of New Education Pioneers and consolidated by the promulgation of the Constitution of 1988. Therefore, it was used as a methodology the literature review and critical analysis of documents and academic productions. It is highlighted the importance of funding policies for achieving the Educational Policies and, in particular, for the implementation of . Thus, it reflects upon the approval of the National Plan of Education and the new possibilities and limits for Educational Funding, and it points to the need of ensuring the NPE accomplishment as one of the tools to effectively implement a National System of Education, especially related to the educational funding targets.